Genre dynamics in teletandem chats: a longitudinal study of english <> portuguese partnerships at UNESP-SJRP - Ferro, Priscilla (The ESPecialist, 2024)
This paper explores the use of chat in Teletandem (TTD) activities (Telles; Vassallo, 2006) on the UNESP-SJRP campus from 2006 to 2020, focusing on possible genres materialized in chats, in English <> Portuguese partnerships. Two main questions guided the study: firstly, to identify the genres materialized in chats; and secondly, to examine how the use of chat has evolved along with synchronous communication tools. The research adopted a qualitative and longitudinal approach (Wagner et. al, 2018; Dörnyei, 2007) and investigated whether textual genres (Bazerman, 1994, 2006; Miller 2012a, 2012b, 2016, 2017; Miller; Shepherd, 2009) emerged in chat interactions. Through this analysis, the use of chats over the period was verified. The data was collected from publications related to TTD, including master's dissertations and doctoral theses, and from MulTeC (Lopes, 2019; Aranha; Lopes, 2019). Once collected, the data was integrated into the technical, ontological and epistemological dimensions (Ferro, 2021). The analysis was conducted based on predefined thematic axes, considering the particularities of the textual genres identified and based on the quantitative results obtained by analyzing the data in the Voyant Tools® tool. The final analysis revealed evidence of the materialization of the Initial Teletandem Oral Session (iSOT) genre (Rampazzo, 2017) in the initial period, which did not carry over into the second period due to advances in synchronous communication tools. However, this possible genre persisted in another form within the tool, indicating potential survival in the new environment. In addition, there was a change in the use of chat from being the main locus of interaction to a supporting role for oral interaction, in line with the evolution of synchronous communication tools over time. Despite these findings, limitations were found, including insufficient data from the initial period. Future avenues of research could explore additional genres within the TTD genre system, investigate the possible migration of genres and analyze the syntactic, semantic and pragmatic consequences of the materialization of genres in chat and vice versa. These new investigations may offer valuable insights for further research into TTD and related linguistic issues.